(untitled) (Chemical Engineering Research Bulletin, 2026)
This paper presents the results from simulation study with different development scenarios of Fenchuganj gas field of Bangladesh. It came into production in 2004 with only one well, which watered out after three years. It was then recompleted in a lower zone but soon water cut became too high, forcing a significant reduction in gas rate for sand free production. A second well is in production since 2005. Two more development wells were also under way. The need for simulation study was obvious at this point, which would provide insight to the production behavior, the state of depletion, and the possible effects of the development wells. The first simulation study was carried out in 2009. However, a second study was carried out later, which is the subject matter of this paper. For the second study, the geological model was revised and was validated by history matching. It reproduced the wellhead pressure and water production history of 7 years with reasonable accuracy. Thus reliability of the model was established, and predictive simulation was run for 25 years up to 2036. Five different development scenarios were simulated, which incorporated the existing wells as well as new wells. The results indicated highest recovery of about 81.75%, with six wells draining the three major sands. Chemical Engineering Research Bulletin: 24 (Issue 1): 70-78